Spatial Organization and Architectural Program of Convention Center for MICE industry in 2nd Tier Destination City in Southeast Asian Region - Klinmalai, Siwaporn; Kaewlai, Peeradorn (Journal of Architectural/Planning Research and Studies (JARS), 2020)
MICE Travelers is a type of large group’s visitors, usually planned well in advance for business and MICE event. Nowadays, the 2nd tier MICE destinations are building new convention center and infrastructure to support corporate and association meetings such as Malaysia, Singapore, and Indonesia. This research aims to study the spatial organization and architectural program of the convention center in the 2nd tier MICE destinations. By analyzing 4 outstanding cases in the ASEAN region in physical characteristics and, space planning of the convention center and number of meetings per city in order to identified the venue layout, hierarchy of accessibility, function, and amenities and used it as supporting data to develop a competitive MICE venue in Thailand that compatible with other city conventions in the region.